Conflict Management in Inter-Governmental Relations in Nigeria: Issues and Prospects - Chima, Emmanuel; Bello, Mojirayo Bukola; Okoroafor, Fidelis Obasi; Obilor, Ogbulafor I (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
ABSTRACT Intergovernmental relation is an interaction among different levels of government. Intergovernmental relation is oftentimes conflict-ridden, and the extent of the conflict depends on how they are managed by the actor operating at the government levels. This study examines conflict management in intergovernmental relations in Nigeria. The content analysis method would be used. This will be carried out by analyzing data obtained from extant literature on the subject matter. This paper found that intergovernmental conflicts mainly borders on tax jurisdiction and revenue allocation. Other areas of conflict were found to include domination by the centre of other units, as well as, parallel and vertical misunderstanding among units on administrative, legal, social, and economic matters. It was suggested that levels of government should introduce such a method as discussion, integration, good management of communication in other to attain a peaceful intergovernmental relations regime.